PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS MASJID DALAM MELAWAN RENTENIR (STUDI MASJID JAMI’ AL-UMARI KELAYU LOMBOK TIMUR NTB) - Hidayatulloh, Muhammad Haris; Amalia, Rizka; Djalaluddin, Ahmad (Indonesian Scientific Journal of Islamic Finance, 2024)
This study aims to examine and analyze how the potential and methods of economic empowerment based on the Jami' Al-Umari Kelayu Mosque, East Lombok, NTB, in fighting loan sharks in the community. This study uses qualitative research using this approach to match empirical reality with applicable theories. The results of the study indicate that with the programs carried out by the mosque and the existing potential, this can provide or contribute to reducing and raising public awareness of the dangers of usury practices themselves. Because the practice carried out in the community is to provide financing to people who have businesses and need capital to develop their businesses themselves. The mosque provides loans with a qardhul hasan contract so that borrowers do not need to provide profit sharing and only return the capital they borrowed.